2006
DOI: 10.1029/2005jb004048
|View full text |Cite
|
Sign up to set email alerts
|

The sedimentary and tectonic evolution of the Yinggehai–Song Hong basin and the southern Hainan margin, South China Sea: Implications for Tibetan uplift and monsoon intensification

Abstract: The Yinggehai–Song Hong basin is one of the world's largest pull‐apart basins, lying along the trace of the Red River fault zone in the South China Sea. South of Hainan Island this basin crosscuts the rifted margin of the northern South China Sea. In this paper we present for the first time a regional compilation of multichannel seismic reflection data from both the strike slip and rifted margins. The basins started to open after ∼45 Ma, especially after ∼34 Ma. The Yinggehai basin was folded and inverted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
199
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 248 publications
(209 citation statements)
references
References 115 publications
(183 reference statements)
4
199
2
4
Order By: Relevance
“…The depositional environment of the Meishan Formation was interpreted to from littoral to neritic delta facies (Gong et al, 1997 Gong et al (1997), Huang et al (2003) and Gong and Li (2004). 15.5 Ma, and increased between 15.5 and 10.5 Ma (Clift and Sun, 2006;Hoang et al, 2010). The pressure coefficient and geothermal gradient can reach 2.0e2.3 and 4.25e4.56 C/100 m, respectively (Zhang et al, 1996;Huang et al, 2002Huang et al, , 2003.…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…The depositional environment of the Meishan Formation was interpreted to from littoral to neritic delta facies (Gong et al, 1997 Gong et al (1997), Huang et al (2003) and Gong and Li (2004). 15.5 Ma, and increased between 15.5 and 10.5 Ma (Clift and Sun, 2006;Hoang et al, 2010). The pressure coefficient and geothermal gradient can reach 2.0e2.3 and 4.25e4.56 C/100 m, respectively (Zhang et al, 1996;Huang et al, 2002Huang et al, , 2003.…”
Section: Geological Settingmentioning
confidence: 99%
“…The pressure coefficient and geothermal gradient can reach 2.0e2.3 and 4.25e4.56 C/100 m, respectively (Zhang et al, 1996;Huang et al, 2002Huang et al, , 2003. The depocenters are mainly controlled by NW-and roughly N-Strending faults (Sun et al, 2003), which show a migration to the southeastern basin between 21 and 16 Ma, which led to basin inversion and formation of an angular unconformity (Rangin et al, 1995;Clift and Sun, 2006). During 16e5.5 Ma, depocenters gradually migrated back to the northwest, and paused in the northwestern basin ).…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Clift and Sun (2006) suggested that the sedimentation rates in the Y-SH Basin increased sharply at the end of the Miocene. Clark et al (2005) used an initiation of the major river incisions to identify the timing of the initial uplift at 13e9 Ma and the high erosion rates between 0.23 and 0.47 mm/yr, and the result does coincide with the thermochronology data published by Xu and Kamp (2000) and Kirby et al (2002).…”
Section: Tectonic Implicationmentioning
confidence: 99%